New species and records of Ischnosoma Stephens (Coleoptera, Staphylinidae, Tachyporinae) from China - Kocian, Matúš; Schülke, Michael (Zootaxa, 2016)
More than 1100 specimens of the genus Ischnosoma Stephens, 1829, from China and Taiwan are revised. In all, 29 species and one subspecies are recognized. Seven new species are described and illustrated: Ischnosoma zipapertum sp. n., I. vicinum sp. n., I. foedum sp. n., I. involutum sp. n., I. yunnanum sp. n., I. abstrusum sp. n., and I. gemellum sp. n. Additional records of previously described species are reported. The distributions of all the species are mapped. Four species, Ischnosoma dicoidale discoidale (Sharp, 1888), I. faciatocolle (Champion, 1922), I. hieroboam Kocian, 2003, and I. rosti (Bernhauer, 1923), are recorded from China for the first time. A revised key to the Ischnosoma species of China and Taiwan is presented.